Keefektifan Lembar Kerja Peserta Didik Berbasis Problem Base Learning Bermuatan Lokal Minangkabau Untuk Pembelajaran Menulis Teks Deskripsi - Apri Pendri; Meksi Rahma Nesti (Jurnal Pendidikan Indonesia (JOUPI), 2023)
The learning of writing descriptive texts plays a crucial role in developing students' language skills. This article aims to investigate the effectiveness of Student Worksheets (LKPD) based on Project-Based Learning (PBL) infused with Minangkabau local content in enhancing the ability to write descriptive texts. This approach is directed at combining practical learning aspects with enriching local content in the effort to achieve optimal learning outcomes. By integrating PBL elements that encourage active student engagement and leveraging the rich Minangkabau local culture, this research seeks to measure the positive impact of this approach on students' writing competency achievement. The research methodology involves student participants from Junior High School level, who participated in a series of learning activities using PBL based LKPD enriched with Minangkabau local content. Data were collected through classroom observations, interviews, and written tests. The results of this study present a PBL-based Problem-Based Learning approach for teaching descriptive text writing. The effectiveness of the LKPD was analyzed, resulting in a score of 83.21% with the category of "very good," as obtained from students' performance test scores.